In vivo pharmacokinetics, biodistribution and antitumor effect of paclitaxel-loaded micelles based on α-tocopherol succinate-modified chitosan. (12th October 2016) - Liang, Na; Sun, Shaoping; Hong, Juan; Tian, Jingzhuo; Fang, Liang; Cui, Fude
Abstract: In our previous study, α-tocopherol succinate modified chitosan (CS-TOS) was synthesized and encapsulated paclitaxel (PTX) to form micelles. Preliminary study revealed that the CS-TOS was a potential micellar carrier for PTX. In this study, some further researches were done using Taxol formulation as the control to evaluate the micelle system deeply. In vitro cell experiments demonstrated that the cytotoxic effect of PTX-loaded CS-TOS micelles against MCF-7 cells was comparable with that of Taxol formulation, and the PTX-loaded micelles had excellent cellular uptake ability, which was in a time-dependent manner. The in vivo pharmacokinetic study in rats showed that the micelles prolonged the half-life and increased AUC of PTX than Taxol formulation. From biodistribution study, it was clear that for micelles, the drug concentrations in the liver and spleen were significantly higher than those of Taxol formulation, but much lower in the heart and kidney. Furthermore, the PTX-loaded micelles showed superior antitumor effect, but yielded less toxicity as indicated by the results of antitumor efficacy study and survival study in U14 tumor-bearing mice. These results suggested that CS-TOS micelles could be a potentially useful drug delivery system to improve the performance and safety of PTX.